Invasive fungal infections in a pediatric hematology-oncology department: A 16-year retrospective study - Nikoleta Kazakou; Timoleon-Achilleas Vyzantiadis; Anastasia Gambeta; Eleni Vasileiou; Eleni Tsotridou; Dimitrios Kotsos; Athina Giantsidi; Anna Saranti; Maria Palabougiouki; Maria Ioannidou; Emmanuil Hatzipantelis; Athanasios Tragiannidis (Mazandaran University of Medical Sciences, 2020)
Background and Purpose: Invasive fungal infections (IFIs) are a major cause of morbidity and mortality in immunocompromised children. The purpose of our study was to evaluate the incidence of IFIs in pediatric patients with underlying hematologic malignancies and determine the patient characteristics, predisposing factors, diagnosis, treatment efficacy, and outcome of IFIs. Materials and Methods: For the purpose of the study, a retrospective analysis was performed on cases with proven and probable fungal infections from January 2001 to December 2016 (16 years). Results: During this period, 297 children with hematologic malignancies were admitted to the 2nd Pediatric Department of Aristotle University of Thessaloniki, Greece, and 24 cases of IFIs were registered. The most common underlying diseases were acute lymphoblastic leukemia (ALL; n=19, 79%), followed by acute myeloid leukemia (AML; n=4, 17%) and non-Hodgkin lymphoma (NHL; n=1, 4%). The crude incidence rates of IFIs in ALL, AML, and NHL were 10.5%, 18.2%, and 2.8% respectively. Based on the results, 25% (n=6) and 75% (n=18) of the patients were diagnosed as proven and probable IFI cases, respectively. The lung was the most common site of involvement in 16 (66.7%) cases. Furthermore, Aspergillus and Candida species represented 58.3% and 29.1% of the identified species, respectively. Regarding antifungal treatment, liposomal amphotericin B was the most commonly prescribed therapeutic agent (n=21), followed by voriconazole (n=9), caspofungin (n=3), posaconazole (n=3), micafungin (n=1), and fluconazole (n=1). In addition, 12 children received combined antifungal treatment. The crude mortality rate was obtained as 33.3%. Conclusion: As the findings of the present study indicated, despite the progress in the diagnosis and treatment of IFIs with the use of new antifungal agents, the mortality rate of these infections still remains high.